Liveness in the Metaverse: The Dramaturgical Role of User-Experience Design in Online Digital Performance - Patti, Federica (Mimesis Journal, 2024)
Some recent digital performances on online platforms make it urgent to reassess the nature of being online, together with a recontextualization of the concepts of reality, simulation, liveness and community. The article proposes the analysis of two examples of digital performance in 3D online environments, following the user experience design philosophy. The experiences were designed by implementing native UX design: artists follow hedonic UX design, associated with highly positive emotions, to subvert the system’s native mental model and imagine non-commercial forms of storytelling, interaction and participation, and to build diverse communities.